PROSPECTIVES IN EDUCATIONAL RESEARCH - Hunka, Steve (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
If educational research is really going to have influence on educational practice, it is about time. Steve Hunka reviews some of the distorting pressures that have affected and are likely to affect confidence in theoretically-based educational research, and prescribes conditions essential for that vital activity. He compares the relative weakness of educational research with the success of the physical sciences, and draws detailed conclusions for special requirements in monitoring and feedback to correct its basic theory. He then turns to a consideration of those human capabilities (such as killing area!) that have recently been extraordinarily extended through technological invention; and in a fascinating sequence he derives from among them some others (distribution of instruction, simulation of events, instructional capabilities) which promise to be peculiarly helpful in the special situation and difficulties of educational research, and which accordingly should be accepted as serving to channel the thrust of its effort.